2022
DOI: 10.3892/ijmm.2022.5166
|View full text |Cite
|
Sign up to set email alerts
|

Connexins and angiogenesis: Functional aspects, pathogenesis, and emerging therapies (Review)

Abstract: connexins (cxs) play key roles in cellular communication. By facilitating metabolite exchange or interfering with distinct signaling pathways, cxs affect cell homeostasis, proliferation, and differentiation. Variations in the activity and expression of cxs have been linked to numerous clinical conditions including carcinomas, cardiac disorders, and wound healing. Recent discoveries on the association between cxs and angiogenesis have sparked interest in cx-mediated angiogenesis due to its essential functions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…In this context, it is important to note that treatment with Cx blocking peptides for short periods of time (< 45 min) only inhibits hemichannel activity, without affecting gap junction channels, which are blocked by longer application of these peptides (> 1 hr) [13,29,30]. In addition, although endothelial cell migration has been associated with changes in gap junction communication [10,24,31], we found that, in mesenteric endothelial cells, the level of intercellular coupling via gap junction was similar in the migration front as compared with that observed in endothelial cells before scratching the intact monolayer (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is important to note that treatment with Cx blocking peptides for short periods of time (< 45 min) only inhibits hemichannel activity, without affecting gap junction channels, which are blocked by longer application of these peptides (> 1 hr) [13,29,30]. In addition, although endothelial cell migration has been associated with changes in gap junction communication [10,24,31], we found that, in mesenteric endothelial cells, the level of intercellular coupling via gap junction was similar in the migration front as compared with that observed in endothelial cells before scratching the intact monolayer (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…4 Instead of the normal blood vessels, tumor neovascularization is characterized by weak vascular wall, extensive vascular endothelial space, high vascular permeability, and structural disorder. 5 Angiogenesis-related factors are often overexpressed in tumors. 6 Neovascularization is immature and highly heterogeneous, leading to reducing immune cell infiltration and activity and increasing the probability of cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…7 Angiogenesis provides additional nutrient supply to tumor cells, so antiangiogenesis is a promising antitumor therapeutic method. 5 Immunotherapy is a promising antitumor strategy and has achieved promising results in many clinical studies. [8][9][10] Immune checkpoint inhibitors for PD-1, PD-L1, and CTLA-4 are used in the molecularly targeted therapy of colon cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations